PESANTREN AS AGENT OF WASATHIYAH ON RESPONDING THE PROBLEMS OF THE INDONESIAN COMMUNITY IN THE SOCIETY 5.0 ERA (CASE STUDY OF ALUMNI ABUYA SAYYID MUHAMMAD BIN ALAWI AL-MALIKI) - Muta’allim Muta’allim; Siti Masyarafatul Manna Wassalwa; Sitti Nuraini; Yuana Dwi Agustin; Damon Wicaksi (International Conference on Humanity Education and Society (ICHES), 2023)
Religious moderation exists as a solutive embodiment of the diversity of society in Indonesia. Islamic boarding schools are institutional institutions where the character of religious moderation is internalized and propagated in society. In this case, alumni of Abuya Sayyid Muhammad bin Alawi al-Maliki are alumni of the Rusaifah Islamic boarding school who have become many figures and have many congregations in the community. This study aims to explore moderation in the religion of alumni Abuya Sayyid Muhammad bin Alawi al-Maliki in responding to the problems of Indonesian society in the era of society 5.0. This research is a field research with a qualitative approach. Data obtained by using data collection instruments in the form of observation, documentation and interviews. Then the data were analyzed by qualitative data analysis using Miles and Huberman's model analysis. The results ofthis study are, first, the concept of religious moderation of alumni Sayyid Muhammad Alawi al-Maliki in responding to the problems of Indonesian society in the era of society 5.0 is in line with religious moderation of ahlus sunnah wal jama'ah ala Islamic boarding schools in the archipelago; second, the concept of religious moderation of alumni Sayyid Muhammad bin Alawi al-Maliki has greatly contributed to building tolerance that is democratic and critical in responding to the problems of Indonesian society in the era of society 5.0.